Reiﬁcation and capitalist sociality: a necessary debate (Emancipação, 2013)
This paper aims to conduct a debate on the theoretical developments of the category of reification as understood by three great contemporary authors in the Social Sciences field: Lucien Goldmann, Herbert Marcuse and Fredric Jameson. The importance of the analysis of these authors is due to both interchange and/or incorporation of the theory of reification developed by the Marxists, and the desire of these intellectuals to contribute to the concrete analysis of the derivations of the reification phenomenon. Thus, our analysis sought to examine the category of reification, comparing it to the examination of concrete phenomena encountered in the social environment in which the above-referred authors are inserted.
Keywords: Reification. Sociability. Capitalist changes.